Low friction and wear characteristics formed by mechanically induced surface nanocrystallization: A review of recent advances - Youwang Tu; Yong He; Lei Zhang; Miao Song (Friction)
Friction and wear of metallic materials are ubiquitous in modern life, resulting in significant energy consumption and property damage. The tribological performance of metallic materials is strongly affected by their surface characteristics, motivating the rapid development of surface treatment technology. As a simple method without changing the matrix composition, mechanically induced surface nanocrystallization has emerged as a promising strategy to achieve reduced friction coefficients and increased wear resistance for metals. This review highlights the systemic progress and prospects of mechanically induced surface nanocrystallization, emphasizing its ability to mitigate friction and wear in metals. This review begins by presenting various processing techniques for preparing surface nanostructures, followed by an in-depth discussion of the mechanisms of mechanically induced surface nanocrystallization and the effects of processing techniques and their parameters on surface nanocrystallization. Then, several methods for stabilizing nanocrystalline (NC) structures are briefly introduced. Furthermore, this review thoroughly examines the influence of surface nanocrystallization on the tribological properties and the underlying mechanisms. Finally, the potential applications and challenges of surface nanostructured configurations in friction- and wear-related fields are thoroughly discussed.